Unravelling the demographic dynamics of ethnic residential segregation. Issue 2 (24th August 2018) - Kauppinen, Timo M.; van Ham, Maarten
Abstract: Selective intraurban migration of ethnic groups is often assumed to be the main microlevel mechanism reproducing ethnic residential segregation. However, other demographic processes, such as natural change and international migration, also matter. This paper contributes to the literature by unravelling the impacts of different demographic processes to changes in ethnic segregation. It uses longitudinal individual‐level register data on the complete population of the Helsinki region in Finland. We calculate observed changes in exposure indices, segregation indices in counterfactual scenarios, and decompositions of population changes. Results indicate that intraregional migration is the main process affecting segregation between Finnish‐origin and non‐Western‐origin populations, but whereas migration of the former increases segregation, migration of the latter decreases it. International migration and natural change among the non‐Western‐origin population are the main processes increasing exposure of the non‐Western‐origin population to other members of the group. No indication is found of a general tendency to "self‐segregate."